Food and feed safety of the Bacillus thuringiensis derived protein Vpb4Da2, a novel protein for control of western corn rootworm - Thomas Edrington; Rong Wang; Lucas McKinnon; Colton Kessenich; Kimberly Hodge-Bell; Wenze Li; Jianguo Tan; Gregory Brown; Cunxi Wang; Bin Li; Kara Giddings (PLoS ONE, 2022)
Western corn rootworm (WCR), Diabrotica virgifera virgifera, LeConte, is an insect pest that poses a significant threat to the productivity of modern agriculture, causing significant economic and crop losses. The development of genetically modified (GM) crops expressing one or more proteins that confer tolerance to specific insect pests, such as WCR, was a historic breakthrough in agricultural biotechnology and continues to serve as an invaluable tool in pest management. Despite this, evolving resistance to existing insect control proteins expressed in current generation GM crops requires continued identification of new proteins with distinct modes of action while retaining targeted insecticidal efficacy. GM crops expressing insecticidal proteins must undergo extensive safety assessments prior to commercialization to ensure that they pose no increased risk to the health of humans or other animals relative to their non-GM conventional counterparts. As part of these safety evaluations, a weight of evidence approach is utilized to assess the safety of the expressed insecticidal proteins to evaluate any potential risk in the context of dietary exposure. This study describes the food and feed safety assessment of Vpb4Da2, a new Bacillus thuringiensis insecticidal protein that confers in planta tolerance to WCR. Vpb4Da2 exhibits structural and functional similarities to other insect control proteins expressed in commercialized GM crops. In addition, the lack of homology to known toxins or allergens, a lack of acute toxicity in mice, inactivation by conditions commonly experienced in the human gut or during cooking/food processing, and the extremely low expected dietary exposure to Vpb4Da2 provide a substantial weight of evidence to demonstrate that the Vpb4Da2 protein poses no indication of a risk to the health of humans or other animals.